A collaborative pharmacist prescribing model for patients with chronic disease(s) attending Australian general practices: Patient and general practitioner perceptions - Matthew Percival; Anne McMurray; Christopher Freeman; Neil Cottrell (Elsevier, 2023)
A collaborative pharmacist prescribing model for patients with chronic disease(s) attending Australian general practices: patient and general practitioner perceptions. Background: Pharmacists working in general practice settings are slowly emerging in Australia, with comprehensive medication reviews forming a large part of their role in optimising pharmaceutical care. In Australia, pharmacists are entirely reliant on general practitioners (GPs) accepting and implementing their recommendations to manage drug related problems (DRPs). The next step is a model where the pharmacist takes on responsibility for implementing some of their recommendations. Aim: To investigate patient and general practitioner perceptions of a collaborative model of care where the pharmacist has increased responsibility in assisting the general practitioner manage patients with chronic conditions. Method: Semi-structured, phone and face-to-face interviews were conducted with a purposive sample of patients and GPs respectively. Data were transcribed by a professional transcription service, collated using NVivo 12 Plus and analysed using Braun and Clarke's thematic analysis. Provisional codes were generated and clustered into categories, from which themes were identified. Results: Eighteen interviews were conducted (12 patients, 6 GPs). Four themes were identified from the patient interview data: pharmacist attributes; acknowledgement of the impact of the pharmacist, understanding of the GP-pharmacist collaborative model; relationships with and attitudes towards medicines and health care providers. Four themes were identified from the general practitioner interview data: pharmacist attributes; relationships with pharmacists; impressions on collaboration; impressions of the pharmacist's recommendations. Patients' and GPs' perceptions of the collaborative model of care overall were positive, acknowledging the advantages of a patient-centred, interdisciplinary approach and the potential benefits to patients. Conclusion: The GP-pharmacist collaborative model was viewed favourably by patients and GPs, with some GPs articulating the value in the pharmacist's increased responsibility as they implemented some recommendations to manage DRPs.